2005
DOI: 10.3201/eid1112.050241
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococci in Companion Animals

Abstract: We determined the molecular characteristics of methicillin-resistant staphylococci from animals and staff at a small animal and equine hospital. Methicillin-resistant Staphylococcus aureus (MRSA) identical to human EMRSA-15 was found in dogs and hospital staff. In contrast, 5 distinct MRSA strains were isolated from horses but not from hospital staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
195
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(210 citation statements)
references
References 14 publications
13
195
0
2
Order By: Relevance
“…On the other hand, the MRSA was negative for genes encoding staphylokinase (SAK), chemotaxis inhibitory protein of S. aureus (CHIPS), C3 convertase inhibitor (SCIN) and staphylococcal enterotoxin A (SEA) (not in this study), which are the four human-specific innate immune modulators typical of strains of human origin (van Wamel et al, 2006). MRSA transmission from both farmed and pet animals to humans has already been reported (Baptiste et al, 2005;O'Mahony et al, 2005;Weese et al, 2006). MRSA transmission from farmed cows to the farm personnel has also been documented (Lee, 2003;Juhasz-Kaszanyitzky et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the MRSA was negative for genes encoding staphylokinase (SAK), chemotaxis inhibitory protein of S. aureus (CHIPS), C3 convertase inhibitor (SCIN) and staphylococcal enterotoxin A (SEA) (not in this study), which are the four human-specific innate immune modulators typical of strains of human origin (van Wamel et al, 2006). MRSA transmission from both farmed and pet animals to humans has already been reported (Baptiste et al, 2005;O'Mahony et al, 2005;Weese et al, 2006). MRSA transmission from farmed cows to the farm personnel has also been documented (Lee, 2003;Juhasz-Kaszanyitzky et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA has also been identified as an emerging disease in horses (Weese et al, 2005a;Weese et al, 2005b;Weese et al, 2006), which might act as a reservoir of rare strains for transmission to humans (Baptiste et al, 2005). The isolation of MRSA from two horses in Canada led to a larger study which revealed the colonisation of 79 hospitalised horses and also of 27 people involved in caring for these animals, strongly suggestive of frequent transmission between horses and humans (Weese et al, 2005b).…”
Section: E Horse Associated Mrsamentioning
confidence: 99%
“…Although S. intermedius is the predominant staphylococcal species in dogs (Biberstein et al, 1984;Hoekstra and Paulton, 2002), S. aureus is also frequently found on the skin or associated with suppurative infections (Kloos, 1990). Dogs may act as a reservoir of MRSA (Baptiste et al, 2005) and have been implicated in causing unexplained relapses in humans previously treated and cleared of MRSA infection (Manian, 2003;van Duijkeren et al, 2003). Strains isolated from humans and dogs have been found to have the same PFGE patterns (Manian, 2003) and SCCmec types (van Duijkeren et al, 2004).…”
Section: F Mrsa In Companion Animalsmentioning
confidence: 99%
“…Colonized veterinary personnel can potentially transmit MRSA to humans or to their equine patients and can contaminate materials. 4,35,41 MRSA was detected in rooms where veterinary students and staff member gather. 30,38 Hand hygiene is considered to be one of the most important infection-control tools in human medicine 28 and has also been shown to limit the number of infections with MRSA in equine clinics.…”
mentioning
confidence: 99%